When the Tension Is Rising: A Simulation-Based Study on the Effects of Safety Incentive Programs and Behavior-Based Safety Management - Sebastian Brandhorst; Annette Kluge (Safety, 2021)
When an organization’s management creates a goal conflict between workplace safety and the profitability of the organization, workers perceive work-safety tension. This leads to reduced safety-related behavior, culminating in higher rates of occupational injuries. In this study, we explored design components of behavior-based safety programs: audit results and process communication, reward and punishment, and the framing of production goals as gains or losses. This allowed us to directly observe the effects of the goal conflicts and of the countermeasures that we designed in this study. We examined the perceived work-safety tension using a simulated water treatment plant in a laboratory study with 166 engineering students. Participants had the task of conducting a start-up procedure. The operators’ goal conflict was created by a choice between a safe and mandatory (less productive) procedure and an unsafe and forbidden (more productive) one. As participants were told that their payment for the study would depend on their performance, we expected that rule violations would occur. We found acceptance of measures and their design as important for rule related behavior. Work-safety tension emerged as a strong driver for violating safety rules. We conclude that safety incentive programs can become ineffective if goal conflicts create work-safety tension.